356 OLDER PERSONS LIVING ALONE IN INTEGRATED CARE: DEPRESSION, LOW EDUCATION AND FUEL POVERTY. (25th October 2022) - Dolphin, H; Dyer, A; Domsa, M; McNally, D; Doyle, M; Keating, J; Noonan, C; McGuinn, C; Ahern, L; Murphy, A; Malone, N; Kennelly, SP
Abstract: Background: An important consequence of population ageing has been the increasing number of older adults who live alone. According to TILDA data, older adults with the lowest levels of education tend to experience most social isolation and there is a strong association between living alone and loneliness. We sought to compare the cohort of patients open to the Integrated Care for Older Persons (ICPOP) team in a University Teaching Hospital serving a community area of approx. 300, 000 population, to this national dataset. Methods: A convenience sample of 174 patients who underwent comprehensive geriatric assessment via domiciliary visit between July 2021-May 2022 by was analysed. Data was anonymised and analysis was performed using SPSS v.27. Results: The average age was 81.5 (±8.1) with 63% women in the sample. Eighty-five older adults i.e. 49% of the sample either lived alone or spent more than 21 hours alone per 24-hour period. Compared to those who live with someone, those who lived alone had higher rates of likely depression as determined by Geriatric Depression Score (6.6 vs 4.8 p=0.007). They were also likely to have less educational attainment, as determined by years spent in full time education (11.81 vs 10.42 42 p= 0.0016) and those living alone had overall less central heating in their homes than those not living alone (64/85 vs 81/89 p=0.0109). There were no significant differences in the rates of polypharmacy, falls, dementia and home ownership between groups. There were higher levels of frailty in the group living with someone than those living alone as determined by Clinical Frailty Scale (6.14 vs 5.23 p<0.001). Conclusion: A high proportion of patients seen by our ICPOP team live alone and have complex care needs that require an innovative, multidisciplinary approach. Financial vulnerability in this group is likely to compound isolation and loneliness.